Upaya Konselor Islami Dalam Penanganan Spiritualitas Pada Korban Trauma Kekerasan Dalam Rumah Tangga - Asti Haryati; Neti Herawati; Betaria Soneta; Sukma Wardani (Program Studi Bimbingan Penyuluhan Islam Fakultas Dakwah dan Komunikasi, 2022)
Research Objectives : The purpose of this paper is to look at the efforts of Islamic counselors in dealing with spirituality in victims of domestic violence.Research Methods : This research uses a descriptive qualitative approach with interviews and documentation.Research Results : 1) The role of Islamic counselors in dealing with trauma victims of domestic violence by approaching them first. Where this can foster enthusiasm in the victim and a discussion approach can be used as an alternative approach in Islamic guidance and counseling; 2) Islamic counselors provide direction and views to clients in a better and constructive direction, so that clients understand and realize the problems they have experienced so far, and try to get closer to Allah SWT by carrying out acts of worship in accordance with the instructions of the Al-Qur'an and the Sunnah of the Prophet ; 3) Islamic counselors provide guidance to victims of domestic violence through family assistance.Conclusion : Islamic counselors focus on changing individual mindsets that are not going well and to reduce changes due to fear and trauma, as well as through family assistance and legal assistance in conducting discussions that can be used as alternative approaches to Islamic guidance and counseling.Implication : Islamic counselors to help recover from trauma conditions for victims of domestic violence. It aims to provide psychological assistance to victims of domestic violence to be able to find and fulfill the meaning and purpose of their lives. Where it is able to make individuals as victims of domestic violence improve close interpersonal relationships, draw closer to Allah SWT, show the value of life, actualize their potential, act and think positively, and take the right attitude about all the disasters they experience.